Making difficult decisions : how to be decisive and get the business done - Shaw, Peter, 1949- (Capstone Pub., 2008)
You are faced with so many difficult decisions. Often your decision making seems random. It can be swayed by different situations and emotions. You need to be more rigorous in the way you make decisions and yet you have very little time to do so. Experience from others who have made tough decisions and a framework to help you do so would be invaluable. The courage to make decisions is sometimes a bit elusive. It is difficult to find the calmness to be able to make and live with those decisions. There is so much that can be learned from the experience of others. After working through this book.